2013
DOI: 10.1530/rep-13-0190
|View full text |Cite
|
Sign up to set email alerts
|

Expression and regulation of secreted phosphoprotein 1 in the bovine corpus luteum and effects on T lymphocyte chemotaxis

Abstract: Secreted phosphoprotein 1 (SPP1) in the bovine corpus luteum (CL) regulates cell function during the transitional periods of luteinization and luteal regression. The objectives were to i) characterize SPP1 expression in the CL throughout the estrous cycle, ii) determine factors that regulate SPP1 expression in luteal cells, and iii) examine the role of SPP1 in lymphocyte chemotaxis, proliferation, and function. SPP1 mRNA was greater in fully functional (d10) CL and late cycle (d18) CL compared with developing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 62 publications
1
9
0
Order By: Relevance
“…Interestingly, IL4 and IL10 augment progesterone production from human luteal cells in vitro [11]. The mRNA for IL10 in luteal tissue was more abundant at Day 10 compared to Day 18 of the estrous cycle [42]. In the present study, luteal cells from midcycle CL increased the proportion of cd T cells synthesizing IL10 and decreased the proportion of cd T cells synthesizing IFNG, but increased the proportion of both IL10 þ and IFNG þ cells in the CD4 þ cell population.…”
Section: Walusimbi and Patesupporting
confidence: 45%
“…Interestingly, IL4 and IL10 augment progesterone production from human luteal cells in vitro [11]. The mRNA for IL10 in luteal tissue was more abundant at Day 10 compared to Day 18 of the estrous cycle [42]. In the present study, luteal cells from midcycle CL increased the proportion of cd T cells synthesizing IL10 and decreased the proportion of cd T cells synthesizing IFNG, but increased the proportion of both IL10 þ and IFNG þ cells in the CD4 þ cell population.…”
Section: Walusimbi and Patesupporting
confidence: 45%
“…The FLI1 gene encodes a critical transcription factor, which regulates gene ETS1 ( Vo et al, 2017 ). The SPP1 gene accounts for establishing and maintaining cellular interactions between steroidogenic and non-steroidogenic cells during the development of corpus luteum ( Poole et al, 2013 ). In addition, the GO categories as well as protein–protein network and expression analysis showed that these genes played an essential role in follicle growth and ovulation of ewes.…”
Section: Discussionmentioning
confidence: 99%
“…OPN transcripts were also detected in bovine ovarian follicles and corpus lutea (Brunswig-Spickenheier & Mukhopadhyay 2003). Recently, results of a detailed study have indicated that OPN is localized in bovine luteal cells during the luteal phase of the estrous cycle and is involved in the development and regression of the corpus luteum (Poole et al 2013). To our knowledge, normal OPN expression in follicular or luteal cells in adult animals has not been reported, except for expression in the bovine ovary.…”
Section: Introductionmentioning
confidence: 93%